ANALYSIS AND CRITIQUE OF THE ISRA'ILIYAT NARRATIVES ON PROPHETS YUSUF AND DAWUD IN JAMI' AL-BAYAN BY IBN JARIR AL-TABARI - Rosyad, Mohammad Ulil; Zahid, Muhammad; Hazar, Ibnu (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
Negative accusations regarding the credibility of Imam Jarir al-Thabari in Tafsir Jami’ al-Bayan, which includes many Israiliyat narrations, are often the discourse of Qur’anic researchers from time to time. But is Imam al-Thabari not careful and indifferent to this? The purpose of this paper is to understand the construction and present a critique of the story of Israiliyat in the book of Jami’ al-Bayan, focusing on the story of the temptation of the Prophet Yusuf as. and the Examination of the Prophet Daud as., which the author examines from various views of scholars and mufassir. The method used in this paper is a qualitative descriptive-based literature approach based on the Story of Israiliyat in the work of Ibn Jarir At-Thabari. The data collection is by collecting several texts that are in accordance with the topics discussed in the form of articles and books and analyzed with keyword analysis techniques, abstracts, and results or conclusions on similar sources. The results found 3 things: First, that in the book of Tafsir Al-Ṭabari there are several narrations that contain Israiliyat; Both shahih, dhaif, until declared rejected. Second, the Narration of Israiliyat in the story of Yusuf’s Temptation and Daud’s trial was declared unacceptable because of historical defects. Thirdly, Regarding the reasoning behind the Israiliyat narrative itself, Imam al-Thabari tries to convey only memorized narrations, the decision on this narrative is left to the reader